High-temperature-resistant aging-resistant high-performance cable material and preparation method thereof

By cross-linking of modified amino resin and epoxy resin and combining modified quartz powder, the cable material has been solved inadequate performance problems in high temperature and aging environment, and high mechanical properties and high volume resistivity are achieved.

CN119859382APending Publication Date: 2025-04-22昆山诺浩五金有限公司

Patent Information

Application Number
CN202510016822.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing cable materials have poor performance in high temperature and aging environments, especially inadequate aging resistance, high temperature resistance and mechanical properties, and low volume resistivity.

Method used

By modifying the amino resin, grafting and copolymerizing introduce double bonds and crosslinking with the epoxy resin to form a complex three-dimensional network structure. At the same time, modified quartz powder is used as filler to improve the aging resistance, high temperature and mechanical properties of the cable material.

Benefits of technology

It significantly improves the aging resistance and high temperature resistance of cable materials, and improves its mechanical properties and volume resistivity, and is suitable for applications in high temperature and special environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230158590000101
    Figure BDA0005230158590000101
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, in particular to a high-temperature-resistant aging-resistant high-performance cable material and a preparation method thereof.The high-temperature-resistant aging-resistant high-performance cable material is prepared from, by mass, 30-50 parts of modified amino resin, 10-20 parts of curing agent, 60-100 parts of epoxy resin, 10-20 parts of filler and 1-5 parts of auxiliaries; the modified amino resin is obtained by introducing double bonds into amino resin through graft copolymerization. The cable material provided by the invention has excellent aging resistance, high temperature resistance, excellent mechanical properties and relatively high volume resistivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber, and in particular relates to a high-temperature resistant and aging resistant high-performance cable material and a preparation method thereof. Background Art

[0002] Cables are usually composed of conductors, insulation layers, shielding layers, filling layers, armor layers, and outer sheaths. Generally, the insulation layer is made of rubber. Although rubber has the advantages of good elasticity and wear resistance, its aging resistance, oil resistance, and heat resistance are poor. Specifically, the rubber molecular chain contains unsaturated bonds. Long-term exposure to sunlight, oxygen, ozone, and other environments will easily cause oxidation reactions, resulting in molecular chain breakage and cross-linking, making the rubber hard, brittle, or sticky, and causing aging phenomena such as cracking and powdering. When the outer sheath of the rubber cable comes into contact with oily substances such as mineral oil, animal and plant oils, the oil molecules will penetrate into the rubber, causing the rubber to swell, changing the original physical properties of the rubber, and causing its strength, hardness, elasticity, and other indicators to decline. If the cable is laid in an oily environment, such as near refineries and gas stations, such problems are likely to occur.

[0003] For example, CN109054157A discloses a high-temperature resistant nano cable material and its preparation method, which relates to the technical field of cable materials. The high-temperature resistant nano cable material is made of the following raw materials: polyethylene resin, modified nano filler, modified polypropylene, elastomer, polyurethane rubber, flame retardant, toughening agent, antioxidant, stabilizer. The high-temperature resistant nano cable material of this application has good mechanical properties, good processing performance, and good heat resistance, but this application is mainly improved by modified nano fillers. However, the one-dimensional nano fillers mainly used in it usually have higher modulus and rigidity. After a large amount of such fillers are filled, the overall rigidity of the composite material is greatly improved, the flexibility is significantly reduced, and the material becomes more brittle, and it is impossible to undergo a large degree of elastic or plastic deformation as before, resulting in poor elongation performance.

[0004] For example, CN111269503A discloses a high temperature and cold resistant wire and cable material and a preparation method thereof, wherein the high temperature and cold resistant wire and cable material comprises the following components calculated by weight: 100 parts of polyvinyl chloride paste resin, 20-60 parts of trioctyl trimellitate, 10-30 parts of di(2-propylheptyl) adipate, 0-5 parts of chlorinated paraffin, 1-5 parts of heat stabilizer, and 1-5 parts of antioxidant. The preparation method comprises the following steps of weighing, mixing, and plasticizing to obtain the high temperature and cold resistant wire and cable material. The wire and cable products of this application have excellent high temperature resistance and cold resistance, form stable chemical bonds in the products, and have extremely low precipitation. Even when the amount of plasticizer used is large, there is almost no tendency for the plasticizer to move out, which overcomes the poor compatibility of DOA and DOS with conventional main plasticizers in the prior art, which may cause precipitation. However, the mechanical properties of the cable material are limited. Its flexibility can be improved by adding plasticizers, but compared with some high-performance engineering plastics, its mechanical strength and modulus are still relatively low. For some cables that need to withstand large external forces or are used in special environments, it may not meet the requirements. The plasticizer used is trioctyl trimellitate, which has an even more limited improvement on the mechanical properties of the material. In addition, since it mainly uses polyvinyl chloride paste resin, its volume resistivity is not good.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a high-temperature resistant and aging-resistant high-performance cable material and a preparation method thereof. The cable material provided by the present invention has excellent aging resistance and high-temperature resistance, and has excellent mechanical properties and a high volume resistivity.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] In the first aspect, an embodiment of the present invention provides a high-temperature resistant and aging resistant high-performance cable material, which comprises the following components by weight: 30-50 parts of modified amino resin, 10-20 parts of curing agent, 60-100 parts of epoxy resin, 10-20 parts of filler, and 1-5 parts of additive;

[0009] The modified amino resin is obtained by introducing double bonds into the amino resin through graft copolymerization.

[0010] In a preferred embodiment, the cable material comprises the following components in parts by mass: 34-48 parts of modified amino resin, 12-17 parts of curing agent, 70-100 parts of epoxy resin, 12-18 parts of filler, and 1-4 parts of auxiliary agent.

[0011] In a preferred embodiment, the preparation method of the modified amino resin is as follows:

[0012] The amino resin, benzoyl peroxide and styrene are mixed and the pH is adjusted to 6-8. After the reaction, the mixture is cooled to obtain a modified amino resin.

[0013] In a preferred embodiment, the amino resin is one or more of urea-formaldehyde resin, melamine-formaldehyde resin, benzoguanamine-formaldehyde resin, and aniline-formaldehyde resin.

[0014] In a preferred embodiment, the mass ratio of the amino resin, benzoyl peroxide and styrene is (10-30): (10-20): (15-25).

[0015] In a preferred embodiment, the reaction conditions are: reaction temperature 60-100° C., reaction time 4-8 h.

[0016] The invention modifies the amino resin and introduces double bonds by graft copolymerization, thereby effectively improving the mechanical properties of the cable material, improving the aging resistance and high temperature resistance of the cable material, and particularly improving the volume resistivity of the cable material.

[0017] It is known that amino resin has high volume resistivity and dielectric strength, can effectively prevent current from passing through, reduce the risk of leakage and short circuit, can meet the insulation requirements of cables at different voltage levels, and ensure the safe operation of cables. At the same time, amino resin can have high tensile strength, bending strength and hardness, but the flexibility of amino resin is poor, which will limit the application of cables in some occasions that require frequent bending or special laying requirements. The present invention introduces double bonds through graft copolymerization, so that it undergoes a cross-linking reaction with epoxy resin to form a more complex three-dimensional network structure, thereby improving the flexibility and impact resistance of amino resin, reducing the brittleness of the material, and reducing the possibility of cracks or breakage of the cable material when subjected to external forces.

[0018] It is also worth noting that when the modified amino resin and the epoxy resin are cross-linked, they have excellent synergistic effects in terms of flexibility, volume resistivity, aging resistance and high temperature resistance.

[0019] In terms of flexibility, amino resin contains some flexible alkyl segments. When cross-linked with epoxy resin, these flexible chains are embedded in the relatively rigid cross-linked network of epoxy resin. It is like adding joints to a hard skeleton, giving the molecular chains more room for movement, allowing the material to buffer and disperse stress through segment movement when subjected to force, reducing brittle fracture and improving flexibility. And the cross-linking of the two is not a simple rigid superposition. Through the proportional mixing of the present invention, it is possible to avoid excessive cross-linking density when the two resins are cured separately. The appropriate cross-linking density allows the material to maintain its basic shape and strength while not being too hard and brittle, ensuring flexibility and adapting to deformation requirements such as bending and stretching.

[0020] In terms of volume resistivity, both epoxy resin and amino resin have good insulation after curing. When cross-linked, their molecules intersperse and entangle with each other, weaving into an extremely dense three-dimensional network. This network has no channels for smooth movement of charges, which greatly hinders carrier migration, improves the overall volume resistivity of the material, and has better insulation performance. In addition, the cross-linking reaction can fill in the tiny pores, cracks and other defects that may appear when each is formed and molded separately. These minor defects may become hidden dangers of leakage, but they can be repaired after cross-linking, further enhancing the material's ability to block current.

[0021] In terms of aging resistance, the ether bonds and hydroxyl groups of epoxy resin interact with the amino and imino active groups of amino resin during the cross-linking process to form a more stable chemical structure. In the face of aging factors such as ultraviolet rays, oxygen, and water vapor, the stable structure reduces the risk of group oxidation and hydrolysis, delaying the decline of material performance. At the same time, the cross-linked network of the two acts as a protective barrier, slowing down the penetration of external corrosive substances into the material. It is difficult for oxygen molecules in the air to penetrate the dense cross-linked layer to attack the internal molecular chains, which enhances the material's anti-aging ability.

[0022] In terms of high temperature resistance, the benzene ring structure in the epoxy resin and some heat-resistant groups in the amino resin synergistically enhance thermal stability after cross-linking. Under high temperatures, the intertwined molecular structures are not easy to soften or decompose, maintaining the shape and performance of the material, withstanding higher temperatures, and broadening the application temperature range of the material. Under high temperature conditions, materials that are not fully cross-linked are prone to produce small molecule volatiles, causing the material to lose weight and deform. The perfect cross-linking of the two locks in small molecules that might otherwise evaporate, allowing the material to maintain stable quality in a high temperature environment.

[0023] In a preferred embodiment, the epoxy value of the epoxy resin is 0.285-0.400 mol / 100g.

[0024] In a preferred embodiment, the curing agent is an acid anhydride curing agent, and the acid anhydride curing agent is one or more of phthalic anhydride and methyltetrahydrophthalic anhydride.

[0025] In a preferred embodiment, the filler is obtained by grafting lignin onto quartz powder.

[0026] In a preferred embodiment, the preparation method of the filler is as follows:

[0027] Mix 2-oxazolidinone and lignin, adjust the pH to 10-12, react once until no more gas is generated, and centrifuge and wash to obtain amino lignin;

[0028] The amino lignin is mixed with quartz powder and added into a solvent, followed by adding tetraisopropyl titanate, and then reacted twice, centrifuged, washed and dried to obtain a filler.

[0029] In a preferred embodiment, the mass ratio of the 2-oxazolidinone to lignin is (10-15):1.

[0030] In a preferred embodiment, the conditions of the primary reaction are: reacting in a reactor at a reaction temperature of 90-110°C.

[0031] In a preferred embodiment, the mass ratio of the amino lignin, quartz powder, solvent and tetraisopropyl titanate is (4-10):(1-2):(100-200):(5-10).

[0032] In a preferred embodiment, the solvent comprises water and ethanol, and the mass ratio of water to ethanol is 1:(1-2).

[0033] In a preferred embodiment, the particle size of the quartz powder is 200-400 mesh.

[0034] In a preferred embodiment, the conditions of the secondary reaction are: reaction temperature is 50-90° C., and reaction time is 2-5 h.

[0035] The present invention firstly chemically modifies lignin to introduce active functional groups such as amino groups, and then combines the amino lignin with the silanol groups on the surface of quartz powder to form a stable chemical bond connection. The quartz powder is modified by grafting lignin, so that the dispersibility and compatibility of the filler in the rubber are improved, and the aging resistance and high temperature resistance of the rubber are further improved. More importantly, the volume resistivity of the rubber is further improved.

[0036] In terms of high temperature resistance, after the amino lignin is bonded with quartz powder, the active groups such as amino groups it contains can react with the rubber molecular chain, and the quartz powder can serve as a physical cross-linking point. The two work together to form a more stable cross-linking network structure in the rubber matrix, restricting the movement of the rubber molecular chain at high temperature, thereby improving the heat resistance of the rubber and reducing the softening and deformation of the rubber at high temperature. The quartz powder itself has a high melting point and thermal stability, and can maintain good physical and chemical properties under high temperature environment, playing a role in skeleton support, and cooperates with the amino lignin to prevent the thermal degradation and cross-linking reaction of the rubber molecular chain at high temperature, so that the rubber can still maintain good mechanical properties and structural integrity at high temperature. In addition, the low thermal expansion coefficient of quartz powder can be transferred to the rubber composite material. When the temperature changes, the bonded material can effectively reduce the dimensional changes and internal stress caused by thermal expansion and contraction of the rubber, and improve the dimensional stability and heat resistance of the rubber under high temperature and temperature alternation environment.

[0037] In terms of aging resistance, the amino lignin itself has certain antioxidant properties. Its amino groups can capture the free radicals generated by rubber during the aging process, inhibiting the oxidation reaction and chain degradation reaction caused by free radicals. After bonding with quartz powder, this antioxidant effect may be enhanced due to the synergistic effect of the two, better protecting the rubber molecular chain from oxidation damage and delaying the aging process of rubber. At the same time, quartz powder can act as a physical barrier in rubber, reducing the contact between external aging factors such as oxygen, moisture, and ultraviolet rays and rubber molecules, and reducing the aging rate of rubber. At the same time, the bonded amino lignin can be filled at the interface between quartz powder and rubber, further enhancing this physical barrier effect and improving the aging resistance of rubber. And the bonded amino lignin forms a stronger intermolecular force with quartz powder and rubber, making the rubber molecular chain less likely to break and degrade during long-term use, thereby improving the aging resistance of rubber and extending the service life of rubber products.

[0038] In terms of improving volume resistivity, quartz powder itself has good insulation properties and high volume resistivity. After being added to rubber, it can significantly improve the volume resistivity of rubber, making the rubber have better electrical insulation. When amino lignin is bonded to quartz powder, this insulation performance will be further enhanced, because the bonding structure can make the dispersion of quartz powder in rubber more uniform, reducing the probability of forming conductive paths, thereby improving the volume resistivity of rubber. In addition, amino lignin can modify the surface of quartz powder to improve the compatibility and bonding between quartz powder and rubber. The modified quartz powder can better play its insulating role in rubber, and it may also increase the surface resistance of rubber, further improving the volume resistivity of rubber. At the same time, the bonded material can form a more stable charge distribution inside the rubber, inhibit the migration and aggregation of charges, and reduce the occurrence of local discharge, thereby improving the volume resistivity and electrical resistance of rubber.

[0039] In a preferred embodiment, the auxiliary agent includes one or more of an antioxidant, a flame retardant, and a light stabilizer.

[0040] In a preferred embodiment, the antioxidant is a hindered phenol antioxidant or a phosphite antioxidant.

[0041] In a preferred embodiment, the flame retardant is one or a mixture of bromide flame retardants, phosphorus flame retardants, nitrogen flame retardants, metal hydroxide flame retardants, metal oxide flame retardants and metal boride flame retardants.

[0042] In a preferred embodiment, the light stabilizer is a benzophenone light stabilizer or a benzotriazole light stabilizer.

[0043] In a second aspect, an embodiment of the present invention provides a method for preparing the high temperature resistant and aging resistant high performance cable material as described above, comprising the following steps:

[0044] The modified amino resin, curing agent, epoxy resin, filler and auxiliary agent are melt-blended, stirred evenly and then extruded and granulated to obtain the cable material.

[0045] In a preferred embodiment, the extrusion is carried out in a twin-screw extruder, and the temperatures of the inlet section, middle section and outlet section of the twin-screw extruder are controlled at 115° C., 135° C. and 125° C., respectively.

[0046] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0047] 1. The present invention modifies the amino resin and introduces double bonds by graft copolymerization, thereby effectively improving the mechanical properties of the cable material, improving the aging resistance and high temperature resistance of the cable material, and especially improving the volume resistivity of the cable material.

[0048] 2. The present invention first chemically modifies lignin to introduce active functional groups such as amino groups, and then combines the amino lignin with the silanol groups on the surface of the quartz powder to form a stable chemical bond. The quartz powder is modified by grafting lignin to improve the dispersibility and compatibility of the filler in the rubber, and further improves the aging resistance and high temperature resistance of the rubber. More importantly, the volume resistivity of the rubber is further improved. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Unless otherwise specified, the reagents mentioned in this example are all commercially available.

[0051] Aniline formaldehyde resin, model Macklin, was purchased from Shanghai Hansi Chemical Co., Ltd.

[0052] Lignin, model RFHC1095, was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.

[0053] Quartz powder, with an average particle size of 300 mesh, was purchased from Lianhe Quartz Powder Company, Donghai County, Lianyungang City.

[0054] Phthalic anhydride was purchased from Hubei Yongkuo Technology Co., Ltd.

[0055] Decabromodiphenylethane flame retardant, model HT-106, was purchased from Shandong Taixing New Materials Co., Ltd.

[0056] Epoxy resin E-39-D was purchased from Chuzhou Huisheng Electronic Materials Co., Ltd.

[0057] Example 1

[0058] This embodiment provides a method for preparing a high-temperature resistant and aging resistant high-performance cable material, comprising the following steps:

[0059] (1) Preparation of modified amino resin:

[0060] By weight, 15 parts of aniline formaldehyde resin, 12 parts of benzoyl peroxide, and 18 parts of styrene were mixed, the pH was adjusted to 7, the mixture was heated at 80° C. for 6 h, and the mixture was cooled to obtain a modified amino resin.

[0061] (2) Preparation of filler:

[0062] By weight, 12 parts of 2-oxazolidinone and 1 part of lignin were mixed, the pH was adjusted to 12 and then reacted in a reactor at a temperature of 95° C. until no gas was generated, and the amino lignin was obtained after centrifugal separation and washing;

[0063] By mass, 5 parts of amino lignin and 1 part of quartz powder with an average particle size of 300 meshes were mixed and added to 150 parts of a solvent, wherein the solvent was a mixture of water and ethanol in a mass ratio of 1:2, and then 8 parts of tetraisopropyl titanate were added to react at a reaction temperature of 80°C for 3 hours, and the filler was obtained by centrifugation, washing and drying.

[0064] (3) Preparation of cable materials:

[0065] By mass, 34 parts of modified amino resin, 12 parts of phthalic anhydride curing agent, 70 parts of epoxy resin E-39-D (epoxy value 0.3 mol / 100 g), 12 parts of filler and 1 part of decabromodiphenylethane flame retardant (model HT-106) were melt-blended, stirred evenly and then extruded in a twin-screw extruder for granulation. The temperatures of the inlet section, middle section and outlet section of the twin-screw extruder were controlled at 115° C., 135° C. and 125° C., respectively, to obtain a cable material.

[0066] Example 2

[0067] This embodiment provides a method for preparing a high-temperature resistant and aging resistant high-performance cable material, comprising the following steps:

[0068] (1) Preparation of modified amino resin:

[0069] By mass, 25 parts of aniline formaldehyde resin, 18 parts of benzoyl peroxide and 23 parts of styrene were mixed, the pH was adjusted to 7, the mixture was heated at 80° C. for 6 h, and the mixture was cooled to obtain a modified amino resin.

[0070] (2) Preparation of filler:

[0071] By weight, 14 parts of 2-oxazolidinone and 1 part of lignin were mixed, the pH was adjusted to 12 and then reacted in a reactor at a temperature of 95° C. until no gas was generated, and the amino lignin was obtained after centrifugal separation and washing;

[0072] By mass, 8 parts of amino lignin and 1.5 parts of quartz powder with an average particle size of 300 mesh were mixed and added to 150 parts of a solvent, wherein the solvent was a mixture of water and ethanol in a mass ratio of 1:2, and then 8 parts of tetraisopropyl titanate were added to react at a reaction temperature of 80°C for 3 hours, and the filler was obtained by centrifugation, washing and drying.

[0073] (3) Preparation of cable materials:

[0074] By mass, 48 ​​parts of modified amino resin, 17 parts of phthalic anhydride curing agent, 100 parts of epoxy resin E-39-D (epoxy value 0.3 mol / 100 g), 18 parts of filler and 1 part of decabromodiphenylethane flame retardant (model HT-106) are melt-blended, stirred evenly and then extruded in a twin-screw extruder for granulation. The temperatures of the inlet section, middle section and outlet section of the twin-screw extruder are controlled at 115° C., 135° C. and 125° C., respectively, to obtain a cable material.

[0075] This embodiment provides

[0076] Comparative Example 1

[0077] The difference between this comparative example and Example 1 is that no epoxy resin is added and the modified amino resin is changed to 104 parts.

[0078] Comparative Example 2

[0079] The difference between this comparative example and Example 1 is that the preparation of the modified amino resin in step (1) is not carried out, and 34 parts of the modified amino resin are replaced by 34 parts of aniline formaldehyde resin.

[0080] Comparative Example 3

[0081] The difference between this comparative example and Example 1 is that the preparation of the filler in step (2) is not carried out, and the filler is replaced by 12 parts of quartz powder with an average particle size of 300 mesh.

[0082] Comparative Example 4

[0083] The difference between this comparative example and Example 1 is that the preparation of the filler in step (2) is not carried out, and the filler is replaced by 12 parts of amino lignin.

[0084] Comparative Example 5

[0085] The difference between this comparative example and Example 1 is that the preparation of the filler in step (2) is not performed, and the filler is replaced by 12 parts of lignin.

[0086] Performance Testing

[0087] 1. The volume resistivity of the cable materials obtained in the examples and comparative examples was tested with reference to GB / T8815-2008. The results are shown in Table 1.

[0088] 2. The tensile strength and elongation at break of the cable materials obtained in the examples and comparative examples were tested with reference to GB / T2951, and then the tensile strength was tested again at 200°C, and the percentage of the ratio before and after the test was calculated. The results are shown in Table 1.

[0089] Table 1 Performance test results

[0090]

[0091] It can be seen from the above performance test results that Examples 1-2 have good mechanical properties and aging and high temperature resistance, and a high volume resistivity, especially Example 2 has the most outstanding comprehensive performance, which is mainly due to the cross-linking of the modified amino resin provided by the present invention with the epoxy resin and the synergistic effect with the filler.

[0092] The comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment in the corresponding performance test. This better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.

[0093] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-temperature resistant and aging-resistant high-performance cable material, characterized in that: The composition comprises the following components by weight: 30-50 parts of modified amino resin, 10-20 parts of curing agent, 60-100 parts of epoxy resin, 10-20 parts of filler and 1-5 parts of auxiliary agent; The modified amino resin is obtained by introducing double bonds into the amino resin through graft copolymerization.

2. The high temperature resistant and aging resistant high performance cable material according to claim 1, characterized in that: The cable material comprises the following components in parts by mass: 34-48 parts of modified amino resin, 12-17 parts of curing agent, 70-100 parts of epoxy resin, 12-18 parts of filler and 1-4 parts of auxiliary agent.

3. The high temperature resistant and aging resistant high performance cable material according to claim 1 or 2, characterized in that: The preparation method of the modified amino resin is as follows: The amino resin, benzoyl peroxide and styrene are mixed and the pH is adjusted to 6-8. After the reaction, the mixture is cooled to obtain a modified amino resin.

4. The high temperature resistant and aging resistant high performance cable material according to claim 3 is characterized in that: The amino resin is one or more of urea-formaldehyde resin, melamine-formaldehyde resin, benzoguanamine-formaldehyde resin, and aniline-formaldehyde resin; And / or, the mass ratio of the amino resin, benzoyl peroxide and styrene is (10-30): (10-20): (15-25); And / or, the reaction conditions are: reaction temperature 60-100° C., reaction time 4-8 h.

5. The high temperature resistant and aging resistant high performance cable material according to claim 1 or 2, characterized in that: The epoxy value of the epoxy resin is 0.285-0.400 mol / 100g; And / or, the curing agent is an acid anhydride curing agent, and the acid anhydride curing agent is one or more of phthalic anhydride and methyltetrahydrophthalic anhydride.

6. The high temperature resistant and aging resistant high performance cable material according to claim 1 or 2, characterized in that: The filler is obtained by grafting quartz powder with lignin.

7. The high temperature resistant and aging resistant high performance cable material according to claim 1, 2 or 6, characterized in that: The preparation method of the filler is as follows: Mix 2-oxazolidinone and lignin, adjust the pH to 10-12, react once until no more gas is generated, and centrifuge and wash to obtain amino lignin; The amino lignin and quartz powder are mixed and added into a solvent, followed by adding tetraisopropyl titanate, a secondary reaction, centrifugal separation, washing and drying to obtain a filler.

8. The high temperature resistant and aging resistant high performance cable material according to claim 7, characterized in that: The mass ratio of the 2-oxazolidinone to the lignin is (10-15):1; And / or, the conditions of the primary reaction are: reacting in a reactor at a reaction temperature of 90-110° C.; And / or, the mass ratio of the amino lignin, quartz powder, solvent and tetraisopropyl titanate is (4-10): (1-2): (100-200): (5-10); And / or, the solvent comprises water and ethanol, and the mass ratio of water to ethanol is 1:(1-2); And / or, the particle size of the quartz powder is 200-400 mesh; And / or, the conditions of the secondary reaction are: reaction temperature is 50-90° C., and reaction time is 2-5 h.

9. The high temperature resistant and aging resistant high performance cable material according to claim 1, characterized in that: The auxiliary agent includes one or more of an antioxidant, a flame retardant, and a light stabilizer; The antioxidant is a hindered phenol antioxidant or a phosphite antioxidant; The flame retardant is one or a mixture of bromide flame retardants, phosphorus flame retardants, nitrogen flame retardants, metal hydroxide flame retardants, metal oxide flame retardants and metal boride flame retardants; The light stabilizer is a benzophenone light stabilizer or a benzotriazole light stabilizer.

10. A method for preparing a high-temperature resistant and aging resistant high-performance cable material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The modified amino resin, curing agent, epoxy resin, filler and additive are melt-blended, stirred evenly and then extruded and granulated to obtain a cable material; The extrusion is carried out in a twin-screw extruder, and the temperatures of the inlet section, middle section and outlet section of the twin-screw extruder are controlled at 115° C., 135° C. and 125° C. respectively.

Citation Information

Patent Citations

  • High-temperature resistant nanometer cable material and preparation method thereof

    CN109054157A

  • High-temperature-resistant cold-resistant wire and cable material and preparation method thereof

    CN111269503A

Cited By

  • Polyvinyl chloride fire-resistant power cable and preparation method thereof

    CN121495270A